The DAPA‐DIET study: Metabolic response to Dapagliflozin combined with dietary carbohydrate restriction in patients with Type 2 Diabetes Mellitus and Obesity—A longitudinal cohort study. Issue 6 (20th October 2022) - Hanson, Petra; Randeva, Harpal; Cuthbertson, Dan J.; O'Hare, Paul J.; Parsons, Nick; Chatha, Kamaljit; Reidy, Gemma; Weickert, Martin O.; Barber, Thomas M.
Abstract: Objective: The cardio‐renal benefits of sodium glucose‐like transporter 2 inhibitor (SGLT2i) therapies have been demonstrated in patients with and without type 2 diabetes. However, no studies have explored the long‐term metabolic effects of SGLT2i, combined with dietary carbohydrate restriction. Our primary objective was to describe long‐term changes in weight, energy expenditure, appetite and body composition after 12 months of Dapagliflozin therapy, with carbohydrate restriction, in people with type 2 diabetes and obesity. Our secondary objective was to assess changes in adiponectin and leptin. Method: This was a 12‐month cohort study in a secondary care setting. Participants ( n = 18) with type 2 diabetes (T2D) and class 3 obesity underwent baseline indirect calorimetry for determination of 24‐h energy expenditure, body composition, fasting serum leptin and adiponectin levels, and appetitive assessments. Following initiation of Dapagliflozin (and dietary carbohydrate restriction), measurements were repeated at monthly intervals up to 12 months. Results: Mean starting weight of participants was 129.4 kg (SD 25.9), mean BMI 46.1 kg/m 2 (SD 8.3) and mean HbA1c 53.9 mmol/mol (14.1). Seventeen participants completed the study; after 12 months of Dapagliflozin and dietary carbohydrate restriction, mean weight loss was 8.1 kg (SD 11.3 kg; p = .009). This was mediated by reduced fat mass (mean loss, 9.9 kg; SD 10.4 kg; p = .002) associated with reduced serum leptin at 12 months (mean reduction 11, 254 pg/ml; SD 16, 075; p = .011). There were no significant changes in self‐reported appetite, 24‐h energy expenditure or serum adiponectin during follow‐up. Conclusion: In this study, combined Dapagliflozin therapy and carbohydrate restriction in patients with T2D and obesity resulted in a significant reduction of body weight and fat mass at 12 months without any discernible changes in energy expenditure or appetite. These results offer a scientific and clinical rationale to conduct an exploratory trial investigating the effects of a low carbohydrate diet combined with SGLT2 inhibitors in patients with T2D. Abstract : SGLT2i leads to a sustained weight loss among patients with type 2 diabetes (T2D), with no changes in energy expenditure in the first 12 months of therapy. Combination of the SGLT2i Dapagliflozin and carbohydrate restriction in patients with T2D and obesity resulted in a significant reduction of weight, fat mass and serum leptin, with no discernible change in energy expenditure or appetite at 12 months. Reduced carbohydrate diet with SGLT2i among patients with T2D and obesity could lead to a more clinically meaningful weight loss without detrimental effect on appetite and energy expenditure. These results offer a scientific and clinical rationale to conduct an exploratory trial investigating the effects of a low carbohydrate diet combined with SGLT2 inhibitors in patients with T2D.